2001
DOI: 10.1128/aac.45.10.2716-2722.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Transfer of CMY-2 AmpC β-Lactamase Plasmids between Escherichia coli and Salmonella Isolates from Food Animals and Humans

Abstract: Escherichia coli is an important pathogen that shows increasing antimicrobial resistance in isolates from both animals and humans. Our laboratory recently described Salmonella isolates from food animals and humans that expressed an identical plasmid-mediated, AmpC-like ␤-lactamase, CMY-2. In the present study, 59 of 377 E. coli isolates from cattle and swine (15.6%) and 6 of 1,017 (0.6%) isolates of human E. coli from the same geographic region were resistant to both cephamycins and extended-spectrum cephalosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
282
3
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(304 citation statements)
references
References 29 publications
17
282
3
2
Order By: Relevance
“…Acquisition of this gene may explain the cross resistance seen among β-lactams in this study. Furthermore, co-residence of multiple resistance genes has been documented in E. coli carrying the bla CMY-2 gene, which may help to explain the resistance seen in the fecal E. coli of the present study to doxycycline, enrofloxacin, gentamicin, and imipenem (Winokur et al, 2001). …”
Section: Antimicrobial Resistancementioning
confidence: 57%
“…Acquisition of this gene may explain the cross resistance seen among β-lactams in this study. Furthermore, co-residence of multiple resistance genes has been documented in E. coli carrying the bla CMY-2 gene, which may help to explain the resistance seen in the fecal E. coli of the present study to doxycycline, enrofloxacin, gentamicin, and imipenem (Winokur et al, 2001). …”
Section: Antimicrobial Resistancementioning
confidence: 57%
“…typhimurium strains carrying indistinguishable CMY-2-encoding plasmids were isolated in Nebraska from a patient and cattle during a local outbreak of salmonellosis, demonstrating that the Salmonella-resistant strain evolved primarily in livestock . Since 1998, Salmonella of human and animal origin were reported to show resistance to expanded-spectrum cephalosporins, in Iowa (Winokur et al, 2000;Winokur et al, 2001). Molecular studies demonstrate the emergence of plasmid encoded CMY-2 β-lactamase in most cephalosporin resistant isolates.…”
Section: Plasmid-mediated Resistance To Expanded-spectrum Cephalospormentioning
confidence: 99%
“…Molecular studies demonstrate the emergence of plasmid encoded CMY-2 β-lactamase in most cephalosporin resistant isolates. During the 1998-1999 periods, nearly 16% of E. coli isolates and 5.1% of Salmonella isolates from clinically ill animals in Iowa produced CMY-2 (Winokur et al, 2000;Winokur et al, 2001). Similar plasmids, carrying the cmy-2 gene were also reported in Salmonella isolated from animals in Illinois (Odeh et al, 2002).…”
Section: Plasmid-mediated Resistance To Expanded-spectrum Cephalospormentioning
confidence: 99%
“…In one study, salmonelas isolated from food animals were found to carry CMY-2, a plasmidmediated AmpC-like β-lactamase (Winokur et al, 2001). Doublet et al (2004) found florR (a florfenicol resistance gene) and bla CMY-2 plasmids to be responsible for resistance to widespectrum cephalosporines in salmonelas isolated from clinical samples, animals and foods in the US.…”
Section: Antimicrobial Susceptibility Profile Of Salmonellamentioning
confidence: 99%